The Use of Social Network Analysis in Knowledge Diffusion Research from Patent Data - Chao-Chih Hsueh; Chun-Chieh Wang (2009 International Conference on Advances in Social Network Analysis and Mining : 20-22 July 2009, 2009)
Patent documents are an ample source of technical and commercial knowledge and, thus, patent analysis has long been considered a useful vehicle for R&D management and technoeconomic analysis. In terms of techniques for patent analysis, citation analysis has been the most frequently adopted tool. In this research, we note that citation analysis is subject to some crucial drawbacks and propose a network-based analysis, an alternative method for citation analysis. By using an illustrative data set, the overall process of developing patent network is described. The main objective is to understand that the knowledge diffuse between institution and countries. The knowledge diffusion networks are described by using critical node, core network, and network measures analysis .This includes identifying key influential players, the knowledge spillover patterns among them, and the overall knowledge spillover efficiency. The proposed framework is applied to the field of liquid crystal display (LCD), including the patent citation networks of assignee and countries. The analysis shows that the Japan is the most important citation center in LCD research and the LG Phillps LCD, Sharp Samsung, Hitachi, IBM, and AUO are central points of knowledge flow.